Polyethyl substituted weakly coordinating carborane anions: a sequential dehydrogenative borylation-hydrogenation route. - Molinos, E; Kociok-Köhn, G; Weller, A (2005)
Polyethylated carborane monoanions based on [closo-CB11H12]- with up to five B-ethyl groups can be prepared by a sequential Rh-catalysed dehydrogenative borylation then hydrogenation.